International Solidarity Fund: Spain : inter-departmental correspondence - Carthy, A. E.
032-0129-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From: A.E. CARTHY To: Mr. H.V. TEWSON Department: International Date: 19th January, 1939. SUBJECT. INTERNATIONAL SOLIDARITY FUND: SPAIN With regard to listing goods sent to Spain in the same way as we shewed in the last Congress Report, SCHEVENELS says that, in view of the fact that recent shipments when notified to him have been described as "xxx tons of foodstuffs, xxx tons of clothing" etc., it has been impossible, for lack of the necessary details, to continue the practice followed in the report of 23rd June. This was the reason why the statement sent in December had to be drawn up in a different way, and a survey, as shewn on page 4, substituted. With regard to the question of currency fluctuation, he said that he appreciated the point we raised about the calculation in terms of sterling. Whether it was possible or not to calculate it accurately he did not know. It needed such familiarity with the shipments and the remittances that he could not entrust the matter to any of his staff, and could not promise to have time himself to attempt it before the summer. 292/946/32/129